2018
DOI: 10.5536/kjps.2018.45.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Energy Levels and Bedding Materials on Performance, Meat Quality and Foot Pad Score of Male and Female Slow-Growing Korean Meat-Type Chicken (Hanhyop 3)

Abstract: Two diet energy levels (high or low) and two bedding material (rice husk or saw dust) treatments were designed for either male or female slow-growing Korean meat-type chicken (Hanhyop 3) to make totally eight treatments for 11∼75 d feeding trial. Body weight gain (BWG) were influenced by energy levels, sex of bird and bedding material type. There were interaction effect among those three factors. Feed intakes (FI) by male bird during each and overall periods were higher than those by female. Diet energy levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Abudabos et al [ 40 ] concluded that increasing the stocking density rate from 28 to 40 kg of BW/m 2 had impingement effects on broiler chicken performance and could jeopardize their welfare. For bedding, it was found that there was not much difference between sawdust and rice husk [ 41 ]; however, choosing a material readily available in the local area was probably the best option in terms of handling.…”
Section: Discussionmentioning
confidence: 99%
“…Abudabos et al [ 40 ] concluded that increasing the stocking density rate from 28 to 40 kg of BW/m 2 had impingement effects on broiler chicken performance and could jeopardize their welfare. For bedding, it was found that there was not much difference between sawdust and rice husk [ 41 ]; however, choosing a material readily available in the local area was probably the best option in terms of handling.…”
Section: Discussionmentioning
confidence: 99%